解方程:1.2X*3-3X=36*2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 08:14:08
解方程:1.2X*3-3X=36*2解方程:1.2X*3-3X=36*2解方程:1.2X*3-3X=36*23.6X-3X=720.6X=72X=72÷0.6X=1201.2X*3-3X=36*23.
解方程:1.2X*3-3X=36*2
解方程:1.2X*3-3X=36*2
解方程:1.2X*3-3X=36*2
3.6X-3X=72
0.6X=72
X=72÷0.6
X=120
1.2X*3-3X=36*2
3.6x-3x=72
0.6x=72
x=120
0.6x=72
x=120
3.6x-3x=72
0.6x=72
x=120
解方程:7x-2x+3x=36
解方程7x-2x+3x=36
解方程:1.2X*3-3X=36*2
解方程x/(x-2)=2x/(x-3)+(1-x)/(x-5x+6)
解方程2x:3=x:
解方程 |x+2|=-3x
解方程 (x+2):x=3:
解方程:(x+2)(x+3)=20,解这条方程
解方程{3X+X+2X=12}3X+X+2X=12
(x^2+x)(x^2+x-3)-3(x^2+x)+8=0解方程
解方程(x-3/x)-(3-x/x+1)=5x-15/2x+2
解方程 x(2x-4)+3x(x-1)=5x(x-3)+8
解方程 3x/x×x-1+x×x-1/3x=5/2
解方程:2(X-3)(X+5)=X平方+(X+2)(X-2)+(X+7)
解方程x(x-1)(x-2)(x-3)(x-4)=24x=?
解方程:(x-2)(x^2-6x-9)=x(x-5)(x-3)
x/(x-2)+(x+1)/(x-6)=2x/(x-3) 解分式方程
解方程:x(3x-4)+2x(x+7)=5x(x-7)+90